1999
DOI: 10.3171/foc.1999.7.6.7
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive retroperitoneal approach for lumbar corpectomy and reconstruction

Abstract: The authors describe two occurrences of idiopathic spinal cord herniation, an entity that has been reported previously in only 11 cases. The patients described in this report presented in midlife with Brown-Sequard syndrome. Computerized tomography myelography and magnetic resonance (MR) imaging showed ventral displacement of the spinal cord with no apparent dorsal mass. Intraspinal cerebrospinal fluid (CSF) flow studies in which phase-contrast pulse sequence cine MR imaging was used displayed a normal pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Direct comparison of operative data and clinical outcomes to previous studies is difficult, as all previous studies include heterogeneous cohorts with regards to spinal level of pathology, disease process, and surgical approach. 8,13,16,20,24,26 Despite these discrepancies, our results compare favorably with results from previous reports. Our average estimated blood loss and length of operation are longer than that reported in the literature.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Direct comparison of operative data and clinical outcomes to previous studies is difficult, as all previous studies include heterogeneous cohorts with regards to spinal level of pathology, disease process, and surgical approach. 8,13,16,20,24,26 Despite these discrepancies, our results compare favorably with results from previous reports. Our average estimated blood loss and length of operation are longer than that reported in the literature.…”
Section: Resultssupporting
confidence: 88%
“…7 Since Eck's original report, several studies have reported good outcomes using the aforementioned "mini-open" lateral approach combined with posterior fixation to perform a corpectomy for burst and compression fractures, vertebral tumors and osteomyelitis, spondylodiscitis, and pseudarthrosis following previous corpectomy. 1,2,6,8,13,16,20,24,27 Our study presented herein presents a pure clinical series of patients who underwent single-level lumbar corpectomies with cage placement through a mini-open, extreme lateral, transpsoas approach supplemented with shortsegment posterior instrumentation. Direct comparison of operative data and clinical outcomes to previous studies is difficult, as all previous studies include heterogeneous cohorts with regards to spinal level of pathology, disease process, and surgical approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential benefits of this approach include decreased perioperative morbidity and pain, expedited ambulation, and earlier discharge from the hospital. [1][2][3][4][5][6][7][8] Vertebral body involvement by trauma, tumors, and infections often necessitate corpectomy and canal decompression followed by spinal reconstruction and stabilization. Expandable corpectomy cages are gaining popularity in reconstructive procedures of the thoracolumbar spine, as newer cage designs allow for the adjustment of cage height in situ to provide controlled distraction and deformity correction.…”
Section: Introductionmentioning
confidence: 99%
“…8,16 Similarly, an entirely retroperitoneal approach is often used to access the middle and lower regions of the lumbar spine (L3-5). 8,9,16 However, the thoracolumbar junction (T11-L2) is considered by many to be a challenging region of the spine to access anteriorly because of the confined space that is further complicated by the intervening diaphragm. 17 Additionally, other investigators have showed that perioperative complications related to anterior spine surgery are often approach-specific phenomena and that the surgeryrelated trauma is associated with postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%